A intuição mística bergsoniana como fundamento da experiência religiosa - Prates, Paulo Henrique (2019)
The research developed in this doctoral thesis seeks to highlight the role of intuition in the construction of a religious experience in Bergson. We start from the hypothesis that intuition can serve as foundation for religious experience. In this way, morality and religion play a fundamental role in order to organize and give meaning to our existence. So it is the religious experience that can save us from the nothingness that continually appears in our existence. The end imposes on us a need to construct meaning. Thus, the thesis tries to go through the intuitive method of Bergson, the way of building this sense